(untitled) (Annals of Medical Research, 2022)
Aim: Seborrheic dermatitis (SD) is a commonly seen chronic inflammatory skin disease that occurs as scaly reddish-brown itchy patches on sebaceous, gland-rich areas of the scalp, face, and trunk. The relation between SD disease and serum IMA (Ischemia modified albumin) levels remains unknown. To investigate the potential role of serum IMA and corrected IMA levels in SD disease. Materials and Methods: Thirty-seven participants who were diagnosed with SD disease and sixty-two healthy subjects (control group) were enrolled in the study. Venous blood samples were collected from each participant, and serum IMA was measured spectrophotometrically using the albumin cobalt binding test. Results: The serum IMA and corrected IMA levels were statistically significant between the groups, and the levels of IMA and corrected IMA were measured as SD patients group 0.70, 0.70 and control group 0.52, 0.51 ABSU (absorbance units), respectively (p<0.05). Moreover, serum IMA and corrected IMA levels were statistically significant between male and female groups in terms of gender as 0.75 and 0.69 ABSU, respectively (p<0,05). Serum albumin levels, age, and BMI (body mass index) were statistically insignificant between these groups. Conclusion: Our results show increased serum IMA and corrected IMA levels in patients with SD. Evaluation of IMA and corrected IMA levels in SD disease may contribute to diagnosis and prognosis. Further and comprehensive studies are needed.